The Implementation Of Social Competence Of Islamic Education Teachers In Character Building Of Student - Safitri, Anisa; Ajahari; Syahmidi (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The rapid development of globalization and modernization has influenced the moral and character formation of students, making the role of teachers increasingly crucial in Islamic religious education teachers are expected to not only deliver religious knowledge but also shape students' character through social competence, including communication, empathy, collaboration, and role-modeling. This study aims to analyze the implementation of the social competence of Islamic Religious Education teachers in fostering students' moral character at SMA NU Palangka Raya. Using a qualitative descriptive approach with a case study method, data were collected through observation, structured interviews, and documentation. The research subjects consisted of one Islamic Education teacher, three homeroom teachers, the vice-principal, and nine students from grades X, XI IPA, and XI IPS, selected purposively. Data were analyzed through reduction, presentation, and conclusion drawing using an interactive model. The results show that Islamic Education (PAI)teachers demonstrated good social competence, reflected in effective communication, adaptability to diversity, collaboration with colleagues, and building harmonious relationships with parents. These competencies significantly contribute to the success of moral education in the school